Regional Cooperation in Europe and Asia - Czarny, Elżbieta; Menkes, Jerzy; Śledziewska, Katarzyna (Współpraca regionalna w Europie i Azji, 2010)
As the prospects for global cooperation and multilateral negotiations arc unclear, many countries and groups of countries look for alternative forms of international cooperation. Their result is the enhancement of regional integration. In this paper we discuss trade relations of two Asian regional groups: Association of South-East Asian Nations (ASEAN) and Asia-Pacific Trade Agreement (Former Bangkok Agreement) (APTA). We compare their performance with the effects of activity of two most important European regional groups: European Union (EU) and European Free Trade Association (EFTA). We study economic potential, openness and trade relations of those four groups of countries and of both continental groups analyzed in the years 1994-2008. We start with an analysis of process of regionalism concentrating attention on regional preferential trade agreements in Asia.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 48-60
Keywords: economic integration; preferential trade agreements; international trade